2014
DOI: 10.1097/npt.0000000000000015
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness and Minimal Detectable Change of the Dynamic Gait Index and Functional Gait Index in Persons With Balance and Vestibular Disorders

Abstract: The DGI and the FGA are responsive to change over time in persons with balance and vestibular disorders. More complex gait measures need to be developed, as close to 50% of the subjects received optimal scores at discharge from a physical therapy exercise program, indicating that these measures have a ceiling effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 18 publications
4
55
0
Order By: Relevance
“…Both the DGI and the FGA were found to be significantly responsive for those patients who show a clinically important change on the DHI. 20 These results suggest that both physical and self-report outcome measures have the ability to detect meaningful change in a vestibular population. Further directions for this study would be to examine the responsiveness of these measures for individuals who have received treatment interventions for vertigo, dizziness, and unsteadiness.…”
Section: Discussionmentioning
confidence: 83%
“…Both the DGI and the FGA were found to be significantly responsive for those patients who show a clinically important change on the DHI. 20 These results suggest that both physical and self-report outcome measures have the ability to detect meaningful change in a vestibular population. Further directions for this study would be to examine the responsiveness of these measures for individuals who have received treatment interventions for vertigo, dizziness, and unsteadiness.…”
Section: Discussionmentioning
confidence: 83%
“…28,31 When interpreting the current findings, it is important to consider that the MCID value for a particular measure may vary depending on the anchor, setting, patient population, and diagnosis. 3 21 Another consideration is that the sample in the study by Marchetti et al 21 was younger (mean ageϭ55 years) than the current sample, so the higher estimate for the FGA MCID value may reflect these younger patients' higher These discrepancies suggest that psychometric properties such as the MCID and the MDC need to be studied from a variety of approaches on a variety of patient groups.…”
Section: Mcid Of the Fgamentioning
confidence: 84%
“…19 Several psychometric properties of the FGA have been established (including good reliability, 17 internal consistency, 17 and moderate concurrent validity 20 ) with other balance measures in patients with vestibular disorders. In addition, Marchetti et al 21 reported an 8-point MCID for the FGA in people with vestibular disorders using an 18-point change on the Dizziness Handicap Inventory (DHI) 22 as the external anchor. This 18-point change on the DHI has been related to standard error of measurement of the instrument and is thought to indicate an improvement in disability level.…”
Section: What New Information Does This Study Offer?mentioning
confidence: 99%
“…The performance on the items of the DGI is measured on a 4-point ordinal scale (0–4), with higher scores indicating better performance and a maximum score of 24 [74]. The psychometric properties of the DGI have been well tested with several reports of reliability, validity, and sensitivity in varied clinical populations, including stroke [7173, 7579, 125], as presented in Table 2. Seven of the eight items on the DGI assessment involve walking adaptability capturing 5 domains of walking adaptability (obstacle negotiation, postural transitions, temporal demands, terrain demands, and maneuvering in traffic) (Table 3).…”
Section: Existing Performance-based Clinical Assessments Of Walkinmentioning
confidence: 99%